Implementasi Pendidikan Karakter Dalam Menumbuhkembangkan Wawasan Kebangsaan Mahasiswa STPkat Santo Fransiskus Assisi Semarang - Franciska Epilia; Hartutik Hartutik; Yustinus Joko Wahyu Yuniarto (Pusat Riset dan Inovasi Nasional, 2023)
Friendships with people from different ethnicities and cultures sometimes lead to invisible conflicts. Problems arise when students from across the region gather and speak their local language even though there are other students who do not understand their language. Ideally when together with people from other regions it would be very good to use Indonesian as a unifying language. In developing national insight, there are three important values ​​that must be implemented, namely sacrifice, equality and kinship. A person's national insight becomes important as a person's perspective on himself as a nation that reflects a sense and spirit of nationalism and is able to maintain his identity as a nation with character. The aims of this study: 1) to describe family values ​​in the campus environment, 2) to describe the values ​​of sacrifice in the campus environment, 3) to describe the values ​​of equality in the campus environment; 4) describe the implementation of national insights for STPKat students. The study used descriptive qualitative methods, data collection techniques, namely data triangulation with interviews and questionnaires, documentation, and observation. The research respondents were students of St. Francis of Assisi College of Pastoral Catechetics (STPKat) Semarang. The results of the study show that: 1) The family values ​​of STPKat students can be applied by implementing an attitude of mutual respect for differences in ethnicity, race, culture and language in friendship relations, 2) the values ​​of sacrifice are carried out by adjusting ethnicity, race, culture and language with friends from other regions and, 3) the value of equality is carried out by recognizing that diversity in STPKat has the same or equal position.